MODIFIKASI PERMAINAN BOLA VOLI (MOPERBOLI) UNTUK MENINGKATKAN AKTIVITAS GERAK DAN TEKNIK DASAR PASSING BAWAH PADA SISWA SD KELAS ATAS - Putra Aji, Anjasmoro Dwi; Widiyatmoko, Fajar Dwi; Prastiwi, Bertika Kusuma (Journal of Sport Science and Education, 2019)
The results of this study have been found: (1) the motion activity of the increase in the pulse rate of students has increased from before to after following the learning of moperboli games, from 37.71% to 62.36% for small scale, and for the large scale from SD N 1 Boja by 37.65 to 62.06 from SD N 5 Metseh by 37.86 to 60.27 and SD N 1 Trisobo by 37.76% to 62.36%, this result also shows conformity to the recommended exercise intensity which is 60-90% of the beats maximum pulse. (2) passing techniques under students students increased the average value from before to after following the learning of moperboli games, for small scale 61.63 to 876.95 and for large scale SD N 1 Boja by 65.63 to 73.01 from SDN 5 Meteseh amounted to 61.38 to 76.82 and SD N 1 Trisobo amounted to 62.68 to 70.23. Conclusion the use of moperboli products in elementary PJOK learning has an influence on the level of student activity and not to influence the basic techniques of passing under students to volleyball learning. Suggestions for elementary school PJOK teachers of Moperboli products can be used as a reference to be able to develop other products within the scope of PJOK learning materials